Closed soilless growing system for producing strawberry bare root transplants and runner tips - Giménez, Gustavo; Andriolo, Jerônimo Luiz; Janish, Djeimi; Godoi, Rodrigo (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to test a closed soilless growing system for producing bare root transplants and runner tips of two strawberry clones, using two categories of substrates. The system used corrugated roofing panels of fiber-cement, over which a substrate layer was used as a growing bed. The nutrient solution was pumped from a reservoir toward the upper end of the roofing panels and drained back to a reservoir. Plant growth and development were determined for two advanced strawberry clones, grown in sand or in Plantmax organic substrate. Growth of the stock plants and the number and dry mass of bare root transplants were similar in the substrates, but bare roots differed in their crown diameters by substrate. For number of runner tips, no significant differences were found in total, small, and medium categories in the substrates. A mean production of about 590 runner tips per square meter and 145 bare root transplants per square meter was obtained. For both clones, a large number of bare root transplants and runner tips of adequate size were produced in the closed soilless growing system using sand or organic substrate.